2017
DOI: 10.6007/ijarbss/v7-i11/3574
|View full text |Cite
|
Sign up to set email alerts
|

Formulating a Game-Based Learning for Accounting Undergraduates as an Alternative Method of Learning

Abstract: Accounting undergraduates may find studying accounting rather challenging as there are many complex aspects in the Malaysian Financial Reporting Standards (MFRS) that need to be understood, hence resulting in poor academic results achievements. Moreover, most of the current teaching pedagogy is still following the traditional methods which is not interesting at all to the Generation Z group of students. Game-based learning (GBL) or gamification seems to be a possible alternative to attract their attention. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Solving Skills (PSS) for students of financial accounting, Microsoft Forms, quiz-based learning, and quiz-based assessments ranging from "strongly disagree" (1) to "strongly agree" (5). The online questionnaire was a 5-point Likert Scale consisting of closed questions.…”
Section: Part C Contained Questions About the Need For Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Solving Skills (PSS) for students of financial accounting, Microsoft Forms, quiz-based learning, and quiz-based assessments ranging from "strongly disagree" (1) to "strongly agree" (5). The online questionnaire was a 5-point Likert Scale consisting of closed questions.…”
Section: Part C Contained Questions About the Need For Problemmentioning
confidence: 99%
“…It is critical to improve financial accounting students' problem-solving skills by listing the chronological order of the development of game-based teaching for accounting students, providing guidelines for developing well-designed educational games, and introducing new game-based activities for teaching and learning [4]. Moreover, the study argued that the element of indulging will eliminate the stress of conventional teaching A previous study showed that studying Malaysian Financial Reporting Standards (MFRS) is challenging for accounting scholars [5]. The most significant strength of this study is content analysis, which is used to develop Game-Based Learning (GBL) for accounting students as an alternate learning approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evidence that GBL is an effective method of teaching is inconsistent and often unreliable, in part because of a reliance on small sample sizes and a focus on undergraduate and WEIRD populations (Alwi, et al, 2017;Kebritchi, et al, 2010;Kosa, et al, 2016). Evaluating GBL in organisational settings can help fill the gaps resulting from this imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…Game-based learning has been gaining widespread adoption due to its success in enhancing students' learning experiences and outcomes. Educators have turned to game-based learning, ranging from digital games to traditional board games (Alwi et al, 2017;Bowen et al, 2021, Carenys andMoya, 2016;Carvalho and Oliveira Neto, 2022;Connolly et al, 2012;Lee et al, 2019;Lopez-Hernandez et al, 2022;Mouse, 2019;Seow and Wong, 2016;Silva et al, 2019;Tan et al, 2021;Voshaar et al, 2022). Silva et al (2019) encouraged educators to introduce games into their curriculum as games can be an effective way for students to learn.…”
Section: Introductionmentioning
confidence: 99%